Evaluation of the relationship between main type traits and longevity in Hungarian Simmental cows - Török, Evelin; Füller, Imre; Vágó, Barnabás; Posta, János (Acta Agraria Debreceniensis, 2022)
The Hungarian Simmental cattle is a dual-purpose breed, having good milk and meat production characteristics. Simmental cows have some other important traits, for example, a longer productive life. The longevity or productive life is the time period between first calving and culling. The conformation contributes to productive life, reproduction, and milk production. The aims of this study were to analyze the longevity of Hungarian Simmental dual-purpose cows, to evaluate the effects of the size of the herd, age at first calving, main type traits (frame, musculature, feet and legs, mammary system), and combination of main type traits (frame and musculature, feet and legs and mammary system). Animal, age at first calving, herd*calving, musculature, the mammary system as well as the combination of mammary system and feet and legs were significant effects on longevity. The highest risk ratio was observed for cows first calved after 31 months. The risk of culling increased with increasing scores of musculature and decreasing scores of the mammary system. The highest risk ratio was estimated in category 11 (lower scores of mammary system with lower scores of feet and legs). In this case, the risk ratio was 36% higher than the reference group.